2008
DOI: 10.1523/jneurosci.0617-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Olfactomedin 1 Regulates Retinal Axon ElongationIn Vivoand Is a Modulator of Wnt Signaling Pathway

Abstract: Olfactomedin 1 (Olfm1) is a secreted glycoprotein belonging to a family of olfactomedin domain-containing proteins. It is involved in the regulation of neural crest production in chicken and promotes neuronal differentiation in Xenopus. Here, we investigate the functions of Olfm1 in zebrafish eye development. Overexpression of full-length Olfm1, and especially its BMY form lacking the olfactomedin domain, increased the thickness of the optic nerve and produced a more extended projection field in the optic tect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 43 publications
0
71
0
Order By: Relevance
“…Our previous results indicated that other members of the family of olfactomedindomain-containing proteins, olfactomedin 1 and olfactomedin 3, also known as optimedin, showed some similarities to the action of Wnt proteins (46,58). Therefore, we tested whether myocilin may act through components of Wnt signaling pathways.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Our previous results indicated that other members of the family of olfactomedindomain-containing proteins, olfactomedin 1 and olfactomedin 3, also known as optimedin, showed some similarities to the action of Wnt proteins (46,58). Therefore, we tested whether myocilin may act through components of Wnt signaling pathways.…”
Section: Resultsmentioning
confidence: 98%
“…Currently, we do not know whether full-length myocilin and myocilin-⌬C perform different biological functions. It has been reported that different forms of olfactomedin 1, with or without the olfactomedin domain, may have distinct roles in neuronal differentiation (55,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wif protein consists of an N-terminal secretion signal sequence (NT), the WIF domain (WD), epidermal growth factor-like repeats (EGFs) and a hydrophilic C-terminus. Human WIF1 binds through its WD to Drosophila Wg, to zebrafish and Xenopus Wnt8 (Hsieh et al, 1999;Kawano and Kypta, 2003), to eight Wnts (including 3a, 4, 5a, 7a, 9a, 11) (Surmann-Schmitt et al, 2009), and to a protein involved in neuronal differentiation, olfactomedin 1 (Nakaya et al, 2008). However, a recent report has shown that human WIF1 binds to Wnts both through the WD and the EGF-like domains (Malinauskas et al, 2011).…”
mentioning
confidence: 99%
“…Both OLFM1 and OLFM4 have been implicated in apoptosis. Mutations in OLFM1 [28] and silencing of OLFM1 resulted in increased apoptosis [29]. OLFM4 may have differing roles depending on the tissue, being antiapoptotic in gastric cancers [30] and growth promoting in pancreas and lung cancer cells [31,21].…”
Section: Discussionmentioning
confidence: 99%